Comprehensive Analysis of a Zinc Finger Protein Gene–Based Signature with Regard to Prognosis and Tumor Immune Microenvironment in Osteosarcoma - Sun, Xiangran; Zheng, Di; Guo, Weichun (Frontiers in Genetics, 2022)
Osteosarcoma is the most common malignant bone tumor that seriously threatens the lives of teenagers and children. Zinc finger (ZNF) protein genes encode the largest transcription factor family in the human genome. Aberrant expression of ZNF protein genes widely occurs in osteosarcoma, and these genes are therefore attractive biomarker candidates for prognosis prediction. In this study, we conducted a comprehensive analysis of ZNF protein genes in osteosarcoma and identified prognosis-related ZNF protein genes. Then, we constructed a prognostic signature based on seven prognosis-related ZNF protein genes and stratified patients into high- and low-risk groups. The seven genes included MKRN3, ZNF71, ZNF438, ZNF597, ATMIN, ZNF692, and ZNF525. After validation of the prognostic signature in internal and external cohorts, we constructed a nomogram including clinical features such as sex and age and the relative risk score based on the risk signature. Functional enrichment analysis of the risk-related differentially expressed genes revealed that the prognostic signature was closely associated with immune-related biological processes and signaling pathways. Moreover, we found significant differences between the high- and low-risk groups for the scores of diverse immune cell subpopulations, including CD8+ T cells, neutrophils, Th1 cells, and TILs. Regarding immune function, APC co-inhibition, HLA, inflammation promotion, para-inflammation, T cell co-inhibition, and the type I IFN response were significantly different between the high- and low-risk groups. Of the seven ZNF protein genes, lower expression of ATMIN, MKRN3, ZNF71, ZNF438, and ZNF597 was correlated with a high risk, while higher expression of ZNF525 and ZNF692 were associated that high risk. Kaplan-Meier survival analysis suggested that lower expression of ATMIN, ZNF438, and ZNF597 and higher expression of ZNF692 were associated with worse overall survival in osteosarcoma. In conclusion, our ZNF protein gene-based signature was a novel and clinically useful prognostic biomarker for osteosarcoma patients.